Desain Aktivitas Sains Berbasis Inkuiri Sederhana untuk Pembelajaran IPA di Rumah: Sintesis Sistematis dan Model ADAPT untuk Konteks Sumber Daya Terbatas - Qahfi, Ashabul (FONDASI: Jurnal Pendidikan Dasar, 2025)
In-home science learning faces significant challenges, particularly in resource- limited areas, leading to declining science competence and difficulties for teachers in designing independent inquiry activities. This article presents a systematic synthesis of design principles and implementation strategies for effective simple inquiry activities for in-home science learning within such contexts. Through a systematic literature review of 42 publications, we found that leveraging everyday contextual materials and visual instructions based on flowcharts are key design principles that enhance accessibility and experimental success. To address the common feeling of incompetence among parents, we highlight the effectiveness of the SCAFFOLD model (Simplified, Collaborative, Accessible, Feedback-oriented, Family-centered, Learning- oriented, Digital-enhanced) and micro-training programs in empowering them as inquiry facilitators. Furthermore, minimalist digital strategies utilizing instant messaging applications proved crucial for bridging resource access gaps, while an authentic triangulated assessment model integrating parent observations, online quizzes, and visual documentation provides a holistic view of students' learning progress. The novelty of this research lies in the first synthesis to integrate a socio-materiality framework into the ADAPT model (Accessible, Digital, Affordable, Practical, Triangulated feedback). This model offers a comprehensive, practical, and sustainable solution to the challenges of science learning in limited environments, ensuring access to high-quality science education regardless of infrastructural and resource constraints.